2009
DOI: 10.1007/s00280-009-1077-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-selective cytotoxicity of benzo[c]phenanthridine derivatives from Toddalia asiatica Lam.

Abstract: This study thus proves the effectiveness of benzo[c]phenanthridine derivatives as anti-cancer agent in vivo for the first time, and discusses the mechanisms responsible for the selective cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 11 publications
3
42
0
Order By: Relevance
“…Therefore, new drugs without significant side effects are absolutely required. For this aim, using medicinal plants with good efficacy and few side effects is a good strategy in comparison with allopathic medicine [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new drugs without significant side effects are absolutely required. For this aim, using medicinal plants with good efficacy and few side effects is a good strategy in comparison with allopathic medicine [6].…”
Section: Introductionmentioning
confidence: 99%
“…1A), a natural bioactive phytochemical alkaloid derived from Zanthoxylum nitidum (Roxb) DC, was initially reported to have significant antioxidant, antifungal, anti-inflammatory, and analgesic bioactivities (15). Subsequent studies proved that nitidine chloride exhibited anticancer potential through the induction of apoptosis in a wide variety of human tumor cell lines, such as lung, breast, liver, oral, and osteosarcoma in vitro (16). Activation of caspase-3 (17), inhibition of topoisomerase y (18), and suppression of human immunodeficiency virus reverse transcriptase (19) have been implicated in niditine-mediated anticancer and immunomodulatory function.…”
Section: Introductionmentioning
confidence: 99%
“…T. asiatica is commonly referred to as ''wild orange tree'' and is widely recognized as a medicinal plant in Africa, India, China and Japan. All parts of the plant are believed to have medicinal properties, and its root, bark, and leaves have been used for the treatment of many diseases including diabetes [1][2][3]. Recent studies have supported the beneficial effects of T. asiatica [4], and Stephen et al clearly showed antidiabetic properties of T. asiatica (ethyl acetate extract from leaves) in streptozotocin-induced diabetic rats [3].…”
Section: Introductionmentioning
confidence: 94%